Bilateral Hilar Lymphadenopathy Due To Chlamydia pneumoniae Infection - Fretzayas, Andrew M.; Moustaki, Maria; Priftis, Kostas N.; Yiallouros, Panayiotis K.; Paschalidou, Maria; Nicolaidou, Polyxeni (My University, 2011)
We here report a 5-year-old boy who presented with cough and bilateral hilar lymphadenopathy with a family history of sarcoidosis. The laboratory investigations did not confirm this diagnosis. The child was serologically proven to have Chlamydia pneumoniae infection. He responded well to a course of erythromycin resulting in complete resolution of his symptoms and the presenting radiographic findings on his initial chest X-ray. Pediatr Pulmonol. 2011,46:1038-1040. (C) 2011 Wiley-Liss, Inc.
Keywords: Chlamydia pneumoniae; Clinical Medicine; Hilar lymphadenopathy; Sarcoidosis